2013
DOI: 10.4028/www.scientific.net/amr.797.691
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Subsurface Damages of Glass Fiber Reinforced Composites

Abstract: The machining methods such as waterjet cutting, milling, grinding, lapping, etc. are usually used to manufacture glass fiber reinforced composites (GFRCs) parts. Damages will be produced unavoidably in the machining process, no matter which machining method is employed. Subsurface damage is one of the important parameters to evaluate the surface layer damages. The detection method for the subsurface damages of glass fiber reinforced glass matrix (glass/glass) composite after machining is researched. The charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This has contributed to inconsistency in holes' tolerance and quality, which have resulted in high scraps, bringing about huge loss to the company. Statistically, it is reported that about 60% of the rejection are due to the defects in the holes [11].…”
Section: Introductionmentioning
confidence: 99%
“…This has contributed to inconsistency in holes' tolerance and quality, which have resulted in high scraps, bringing about huge loss to the company. Statistically, it is reported that about 60% of the rejection are due to the defects in the holes [11].…”
Section: Introductionmentioning
confidence: 99%
“…4 In this study, GF serves as a lubricant whereas MoS 2 serves as a crack expansion inhibitor. 46 The extension direction of the extended cracks changed to the sliding surface when they came into contact with GF, producing finer debris. Additionally, during the frictional wear of the composite, the GF on the friction surface functions as a support load, significantly lowering the wear rate of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of [8] present results of their study of near-surface damages in workpieces of glass-fiber composite materials but the conditions for obtaining quality surfaces are not reported because the authors failed to generalize laws of tool action on anisotropic medium with pronounced plastic-elastic properties. The authors consider the medium dense (in contrast to non-dense carbon-carbon composites for which this feature is decisive).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%